Diminishing Sea Ice in the Arctic Presents Challenges and Opportunities. (30th July 2013) - Showstack, Randy
Abstract : With ice diminishing in the Arctic—and with a nearly ice‐free summer Arctic Ocean predicted by 2050 if not sooner—the dramatic and fast‐paced changes in the region present significant challenges as well as opportunities, according to experts and politicians at the 5th Symposium on the Impacts of an Ice‐Diminishing Arctic on Naval and Marine Operations, held in Washington, D. C., on 16–18 July. Among the challenges addressed at the symposium—which was hosted by the U.S. National Ice Center and the U.S. Arctic Research Commission—are preparing for dramatic environmental changes; balancing environmental protection with energy production, mineral extraction, and other industrial uses; meeting an increasing need for scientific research to better understand the region; and dealing with an increasing amount of northern maritime traffic.